2007
DOI: 10.3748/wjg.v13.i4.503
|View full text |Cite
|
Sign up to set email alerts
|

Chromosome 11 aneusomy in esophageal cancers and precancerous lesions- an early event in neoplastic transformation: An interphase fluorescencein situhybridization study from south India

Abstract: which may play a role in the neoplastic transformation of esophageal precancerous lesions to cancers. INTRODUCTIONMore than 30% of the adult population exhibits upper gastrointestinal tract disorders associated with symptoms such as regurgitation, heartburn and dysphagia, warranting an endoscopic evaluation. Some of these esophageal pathologies require medication while others can be managed by altering life-style and dietary habits. A certain percentage of these, however, progress into esophageal malignancies… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
4
0

Year Published

2008
2008
2014
2014

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 22 publications
(23 reference statements)
1
4
0
Order By: Relevance
“…High frequency of chromosomal aneuploidy, attributed to an impaired Aurora A gene reported in many cancers, was also seen in esophageal cancers and precancers as reported from our group (Marumoto et al, 2003;Mohan et al, 2007). It has been suggested that p53 interacts with Aurora-A to suppress its oncogenic activity in a transactivation-independent manner (Chen et al, 2002).…”
supporting
confidence: 82%
“…High frequency of chromosomal aneuploidy, attributed to an impaired Aurora A gene reported in many cancers, was also seen in esophageal cancers and precancers as reported from our group (Marumoto et al, 2003;Mohan et al, 2007). It has been suggested that p53 interacts with Aurora-A to suppress its oncogenic activity in a transactivation-independent manner (Chen et al, 2002).…”
supporting
confidence: 82%
“…Measurement of DNA damage using genotoxicity assays has been known as a crucial approach for understanding the carcinogenesis and assessing the risk of cancer incidence. 22 , 23 This review will discuss the significance of in vivo comet assay and in vivo MN assay for testing genotoxicity and predicting carcinogenic potential ( Fig. 1 ).…”
Section: Introductionmentioning
confidence: 99%
“…For example, hTERT expression together with loss of heterozygosity (LOH) represent early events in lung carcinogenesis, as both were detected in precancerous lesions and in normal epithelium of heavy smokers (Capkova et al, 2007). Presence of chromosome 11 aneusomy in esophageal cancers and pre-cancerous lesions has been reported as an early event in neoplastic transformation (Mohan et al, 2007). Based on the finding of loss of heterozygosity (LOH) of RPL14 that was common in the dysplasia (preneoplastic lesions), malignant tissues and histologically normal epithelia, this genetic change has been reported as an early event in the tumorigenesis of esophagus (Huang et al, 2006).…”
Section: Discussionmentioning
confidence: 98%